Volume 2: Mechanics and Behavior of Active Materials; Structural Health Monitoring; Bioinspired Smart Materials and Systems; En 2018
DOI: 10.1115/smasis2018-8012
|View full text |Cite
|
Sign up to set email alerts
|

Validation of Impedance-Based Structural Health Monitoring in a Simulated Biomedical Implant System

Abstract: Total Knee Replacement (TKR) is an important and in-demand procedure for the aging population of the United States. In recent decades, the number of TKR procedures performed has shown an increase. This pattern is expected to continue in the coming decades. Despite medical advances in orthopedic surgery, a high number of patients, approximately 20%, are dissatisfied with their procedure outcomes. Common causes that are suggested for this dissatisfaction include loosening of the implant components as well as inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…For instance, Tabrizi et al [27] and Ribolla et al [28] used numerical models and experiments to demonstrate the viability of using piezo-transducers in a dental implant to evaluate the stability condition after insertion. Ponder et al [29] presents experimental tests where electrical impedance measurements are taken for assessing a bone-implant interaction that emulates a total knee replacement case. Results showed that the progressive induced damage on the implant was detected with the electrical sensitivity of the piezo transducers.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Tabrizi et al [27] and Ribolla et al [28] used numerical models and experiments to demonstrate the viability of using piezo-transducers in a dental implant to evaluate the stability condition after insertion. Ponder et al [29] presents experimental tests where electrical impedance measurements are taken for assessing a bone-implant interaction that emulates a total knee replacement case. Results showed that the progressive induced damage on the implant was detected with the electrical sensitivity of the piezo transducers.…”
Section: Introductionmentioning
confidence: 99%
“…The application of EMI to the medical field, however, has received less attention. Preliminary work in our research group demonstrated the EMI method to be effective toward detecting degradation of the cement interface in a geometrically simple system comprised of common TKR materials (Ghattas et al, 2019; Ponder et al, 2018). In a related set of works, Rizzo et al investigated the use of impedance SHM to assess the integrity of dental implant fixation (Boemio et al, 2011; Ribolla and Rizzo, 2015; Ribolla et al, 2015; Tabrizi et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Reduction in the shock absorption capacity of the knee as a result of meniscus tear and meniscectomy is also investigated as a non-invasive measure of the joint health [24]. Another application proposed for the vibration measurement is the osseointegration assessment of medical implants such as dental implants [25][26][27], cementless hip implants [28,29], and cemented total knee replacements [30,31] during and after surgery.…”
Section: Introductionmentioning
confidence: 99%